FORMATION OF THE CULTURE OF COMMUNICATION AS A MEANS FORMATION OF PROFESSIONAL COMPETENCE OF THE FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2008)
In article problems of formation of culture of dialogue as way of formation of professional competence of the future teachers are considered.